Islam wasathiyah value in photojournalism in Guo Ji Ri Bao newspaper - Dewi Rahmayuni; Arief Tri Setiawan; Andi Faisal Bakti (Islamic Communication Journal, 2022)
Photojournalism is one of the various channels to convey messages in visual form. It is a combination of images and texts that produces a single communication unit that reflects events and issues in a society. In the A8 section of Guo Ji Ri Bao, a Mandarin-language newspaper in Indonesia, dated September 25, 2020, seven photojournalism materials were discovered to contain signs and symbols related to Islam Wasathiyah value. This implied message indicated the media’s “agenda” in presenting reality or social issues, where the agenda typically corresponds to the ideology of the media itself. The media construct the frame of mind for their readers even with symbols and this study originated with the formulation of the main problem: “How is the value of Islam wasathiyah reflected in photojournalism on the Guo Ji Ri Bao newspaper viewed from the perspective of meanings and media?” An analysis of semiotics, structuralism, connotation and denotation based on Gill Branston and Roy Stafford's Meanings and Media perspective were utilized in this study. It was discovered that Guo Ji Ri Bao newspaper played a significant role in conveying the value of Islam Wasathiyah. This value is important to convey to all levels of society even through photos because it will be one of the ways to preach (da’wah) that lead us to a happy, peaceful, and harmonious life.***Foto jurnalistik merupakan salah satu saluran penyampai pesan dalam bentuk visual. Foto jurnalistik terbentuk sebagai kombinasi dari gambar dan teks yang menghasilkan satu kesatuan komunikasi yang mencerminkan makna tersendiri dan permasalahan dalam masyarakat. Pada media Guo Ji Ri Bao surat kabar berbahasa Mandarin di Indonesia, pada rubrik A8 25 September 2020, ditemukan tujuh materi foto jurnalistik yang memuat tanda dan simbol terkait nilai Islam wasathiyah. Pesan yang tersirat ini berkaitan dengan “agenda” media dalam  menyajikan realitas atau isu-isu sosial yang terjadi. Agenda sebuah media erat kaitannya dengan ideologi media itu sendiri. Sehingga, media kerap mengkonstruksi bingkai pemikiran pembacanya bahkan dengan unsur simbol dan tanda sekalipun. Studi ini hadir dengan rumusan masalah utama: “Bagaimana nilai Islam wasathiyah dalam foto jurnalistik pada surat kabar Guo Ji Ri Bao dalam perspektif meanings and media, dengan fokus menggali aspek semiotika, strukturalisme, dan makna konotasi dan denotasi berdasarkan perspektif makna dan media karya Gill Branston dan Roy Stafford. Kesimpulan pada penelitian menyatakan bahwa surat kabar Guo Ji Ri Bao memainkan peran penting dalam menyampaikan nilai-nilai Islam wasathiyah. Nilai ini penting untuk disampaikan kepada seluruh lapisan masyarakat bahkan melalui foto karena akan menjadi salah satu corong dakwah untuk mengantarkan kita pada tatanan kehidupan yang aman, damai, tenteram, dan bahagia.